Attentional Orienting by Non-informative Cue Is Shaped via Reinforcement Learning - Cho, Sang A.; Cho, Yang Seok (Frontiers in Psychology, 2020)
It has been demonstrated that a reward-associated stimulus feature captures attention involuntarily. The present study tested whether spatial attentional orienting is biased via reinforcement learning. Participants were to identify a target stimulus presented in one of two placeholders, preceded by a non-informative cue at the center of the display. Importantly, reward was available when the target occurred at a location cued by a reward cue defined as a specific color (Experiments 1 and 3) or color-direction combinations (Experiment 2). The attentional bias by the reward cue was significantly increased as trials progressed, resulting in a greater cue-validity effect for the reward cue than the no-reward cue. This attentional bias was still evident even when controlling a possibility that the incentive salience of the reward cue color modulates the cue-validity effect (Experiment 2), or when the reward was withdrawn after reinforcement learning (Experiment 3). However, it disappeared when the reward was provided regardless of cue validity (Experiment 4), implying that the reinforcement contingency between reward and attentional orienting is a critical determinant of reinforcement learning-based spatial attentional modulation. Our findings highlight that a spatial attentional bias is shaped by value via reinforcement learning.